The relationship between service quality and outpatient satisfaction at the obstetrics polyclinic of Lubai Ulu Regional Hospital in 2025 - Fitriko, Sismaya; Jasmi, Jasmi; Aprilina, Aprilina (Institute Of Computer Science (IOCS), 2025)
Background: The quality of health services is a crucial aspect that affects public health and patient satisfaction. At Lubai Ulu Regional Hospital, focusing on the interaction between medical personnel and patients is important in an effort to meet patient expectations and improve the quality of services. Research Objectives: This study aims to determine the relationship between service quality and outpatient satisfaction at the Obstetrics Polyclinic of Lubai Ulu Regional Hospital in 2025. Research Methods: The type of research used is observational with an analytical survey approach with a cross-sectional design. Sampling was carried out by accidental sampling, involving 34 outpatients. Data were collected through questionnaires and analyzed using the Chi-Square test. Research Results: The results showed that 76.5% of patients rated the quality of service as good, with 67.6% of patients being satisfied with the services provided. The Chi-Square test showed a p-value of 0.000, which means that there is a significant relationship between service quality and patient satisfaction. Conclusion: There is a significant positive relationship between the quality of health services and patient satisfaction at the Obstetrics Polyclinic of Lubai Ulu Regional Hospital. Improving the quality of services must be a priority to increase patient satisfaction and the number of visits to the hospital.